2019
DOI: 10.3390/data4020049
|View full text |Cite
|
Sign up to set email alerts
|

A Dataset of Vietnamese Junior High School Students’ Reading Preferences and Habits

Abstract: Books are the invaluable, colossal storage of mankind’s immense scholarship and are still commonly perceived as a more reliable source of knowledge even in this age of digitized information. Extensive reading is often promoted as being vital to cognitive development, especially for students in primary and secondary education. While it could now be considered common knowledge that reading is highly beneficial, reading habits vary among individuals in the same culture and receiving the same public education. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 20 publications
0
16
0
5
Order By: Relevance
“…This finding might have to do with the nature of the favorite pastimes themselves. Vuong, Le, La, Vuong, Do, Vuong, Do, Hoang, Vu, Ho and Ho [70] already reported that female and male differed in terms of hobby preferences. Table 5 presents the differences in more details.…”
Section: Interceptmentioning
confidence: 93%
See 4 more Smart Citations
“…This finding might have to do with the nature of the favorite pastimes themselves. Vuong, Le, La, Vuong, Do, Vuong, Do, Hoang, Vu, Ho and Ho [70] already reported that female and male differed in terms of hobby preferences. Table 5 presents the differences in more details.…”
Section: Interceptmentioning
confidence: 93%
“…The dataset consists of 1676 observations, a subset of the data obtained through the survey "Studying reading habits and preference of junior high school students in Vietnam" [70]. The study was conducted by Vuong and Associates office, from December 2017 to January 2018.…”
Section: Datasetmentioning
confidence: 99%
See 3 more Smart Citations